The puppeteers : the people who control the people who control America - Chaffetz, Jason, 1967- (Broadside Books, 2023)
"Chaffetz explains how nonprofit leaders, union bosses, global CEOs, and many unelected leaders have worked in parallel with the aims of "permanent Washington.""--